Doctors for the truth: Latin American antivaccine oppositional cultures on Telegram - Eduardo Paz Díaz; Paola Ricaurte (Big Data & Society)
The antivaccine hesitancy movement represents a challenge to public policy and platform regulations. During COVID-19, various Latin American antivaccine groups clashed with official sanitary initiatives. Despite many responses, little progress has been made in reaching these groups to transform their perceptions about the benefits of the COVID-19 vaccine. During the pandemic in Latin America, the antivaccine network Médicos por la Verdad (Doctors for the Truth) gained prominence in various countries. Finding itself limited by legal and technical restrictions, this network used alternative media such as Telegram to disseminate messages. This study argues that such groups may be considered an antivaccination culture that opposes government measures. This focus emphasizes narrative construction and allows us to understand the phenomenon from the collective meaning-making perspective. This study analyzed 232,638 Telegram messages from 14 public channels associated with the Médicos por la Verdad network. Our findings indicate that this antivaccine network builds an oppositional culture expressed and reinforced through multimodal, trans-media, fragmented narratives and suspends disbelief that constructs a world where the community enacts a truth pact. These narrative methods foster building a resilient network of oppositional cultures, decreasing the effectiveness of policies. We conclude that research beyond the framework of misinformation and the analysis of conventional platforms is needed to understand the antivaccine oppositional cultures.